Measurement of corneal thickness using Pentacam HR versus Nidek CEM-530 specular microscopy - Maddalena De Bernardo; Palmiro Cornetta; Giuseppe Marotta; Giulio Salerno; Ilaria De Pascale; Nicola Rosa (Journal of International Medical Research, 2020)
Objective To compare corneal thickness (CT) measurements using the CEM-530 (Nidal, Gamagori, Japan) and Pentacam HR (Oculus, Wetzlar, Germany). Methods The CT of 209 healthy subjects (209 right eyes) aged 24 to 89 years (71.35 ± 10.72 years) was measured at the corneal apex (CA), pupil center (PC), and thinnest point (TP) with the Pentacam HR and at the corneal center with the CEM-530 in random order at the same time of day. Results A good correlation but statistically significant difference was found between the CEM-530 and Pentacam HR measurements at the CA (6.10 ± 8.12 µm, R 2  = 0.8947), PC (7.46 ± 8.57 µm, R 2  = 0.8826), and TP (12.44 ± 10.04 µm, R 2  = 0.8392). Comparison of the two devices produced the following regression formulas: y = 0.8859x + 57.644 for the CA, y = 0.8852x +56.657 for the PC, and y = 0.8557x + 68.148 for the TP, where x is the CT obtained with the CEM-530 and y is that obtained with the Pentacam HR. Conclusions These findings indicate that the CEM-530 produces a thicker corneal measurement than the Pentacam HR. The herein-proposed correcting factors are needed to reliably compare these devices.